USING YOUTH SLANGS AMONG TEENAGERS IN SOCIAL MEDIA - Alimov Hasan Xamid o’g’li; Qodirova Munisa Erkinjon qizi (Journal Park Publishing, 2023)
This article explores the growing trend of using youth slangs by teenagers in social media. The author highlights how this trend has become a common language among teenagers in digital communication, leading to the creation of new words and phrases that are not readily understood by adults. With its focus on the intersection of language, culture and social media use, this article offers valuable insights into the ways in which youth slangs are shaping the communication practices of young people today.
Keywords: social media, abbreviation, slang, teenagers, informal language, Generation Z, iGen, GI Generation, Silent Generation.